Case report: Exploring the utility of whole-body bone scintigraphy for pediatric Langerhans cell histiocytosis: insights from clinical practice - Song, Wenyu; Hu, Fan; Shi, Wei; Wang, Fang; Zhang, Yongxue; Lan, Xiaoli; Xia, Xiaotian (Frontiers in Oncology, 2024)
Purpose This mini-review delves into the realm of Langerhans cell histiocytosis (LCH) in children, focusing on its skeletal involvement. By synthesizing pertinent literature, we sought to provide a comprehensive understanding of LCH's clinical and radiographic spectrum. Our study then demonstrates the diagnostic prowess of whole-body 99mTc-methyl diphosphonate (MDP) scintigraphy in LCH cases, underscoring its value in tandem with existing knowledge. Methods Our approach involved an extensive literature review that contextualized LCH within the current medical landscape. Subsequently, we presented a case series featuring five pediatric instances of skeletal LCH, one accompanied by soft tissue infiltration. The principal aim was to illuminate the diagnostic and staging potential of whole-body 99mTc-MDP scintigraphy, augmenting existing insights. Results Through meticulous literature synthesis, we highlighted pediatric LCH's protean clinical manifestations and radiological variability. Aligning with this spectrum, our case series underscored the role of 99mTc-MDP scintigraphy in diagnosing and staging LCH. Among the five pediatric cases, one demonstrated concurrent soft tissue involvement. This aligns with the multifaceted nature of LCH presentations. Conclusions Pediatric LCH can present with a wide range of clinical and radiologic features. By amalgamating our cases with extant literature, we stress the necessity of a multimodal strategy. 99mTc-MDP scintigraphy emerged as an indispensable tool for accurate staging and soft tissue detection. Our findings collectively advocate for a holistic approach to managing LCH, ensuring informed therapeutic decisions for optimal patient outcomes.